PENGEMBANGAN SDM UNTUK IMPLEMENTASI MANAJEMEN RISIKO: PERSPEKTIF BARU DARI SUDUT PANDANG PENGGUNA: HRD FOR RISK MANAGEMENT IMPLEMENTATION: A NEW PERSPECTIVE FROM THE USERS’ POINT OF VIEW - Dominicus Savio Priyarsono; Yusuf Munawar (School of Business, Bogor Agricultural University (SB-IPB), 2020)
The very rapid development of risk management (RM) implementation in private sector industries as well as public sector organizations suggests a strong indication that RM has really succeeded in creating values for its implementers. The ultimate objective of this study is to formulate the best strategy that can effectively help organizations in adopting and improving the quality of RM implementation to enhance their performances. To achieve the objective, for two months (December 2019 through January 2020), this study applied the method of survey involving 309 respondents from various industrial sectors and position levels in organizations. The statistical technique used in this study was the contingency table analysis. The main findings of this study are (1) RM implementation can improve the economic competitiveness of the RM implementing organizations as well as their personnel, (2) the quality of RM human resource development positively effects the quality of RM implementation, and (3) RM competence certification improves the quality of RM trainings and in turn boosts the quality of RM human resource development. Based on the findings it is recommended that higher priority be put to RM human resource development (HRD) as a strategy to improve the quality of RM implementation. Keywords: risk management, human resource development, training, certification of competence, performance